Go all iPad, all the time. IN Features. - Curthoys, Paul.; Hayward, Andrew; Simon, Michael; Vargus, Nic.
A computer magazine advocating ditching your laptop for an iPad? It's not just possible -- it's awesome!
Keywords: iPad (Computer); iOS (Electronic resource); Syncing; iMessages; iPad apps